2010
DOI: 10.1590/s1413-86702010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of treatment for surgical site infections in cases of total knee arthroplasty in a tertiary public hospital in Brazil

Abstract: We declare no confl ict of interest. ABSTRACTThe aim of this study was to estimate the additional cost of treatment of a group of nosocomial infections in a tertiary public hospital. A retrospective observational cohort study was conducted by means of analyzing the medical records of 34 patients with infection after total knee arthroplasty, diagnosed in 2006 and 2007, who met the criteria for nosocomial infection according to the Centers for Disease Control and Prevention. To estimate the direct costs of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
0
11
0
2
Order By: Relevance
“…Through the literature review performed, we identified the main costs caused by HAI in hip and knee arthroplasties and the costs of some treatments and prevention methods for these situations. In agreement with the current state of the art, this review identified LOS as the indicator most commonly used to estimate the direct costs of SSIs, and according to some authors, this happens because, in addition to the direct relationship between the LOS and the risk of HAI, the extension of hospitalization days is an easily understood measure either by physicians or by hospital managers, which translates in the consumption of health resources to treat a complication [21,35,43]. According to Plowman [6], patients who developed HAI remained in hospital 2.5 times longer and incurred hospital costs almost three times higher, when compared with an uninfected patient who underwent the same surgical procedure.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Through the literature review performed, we identified the main costs caused by HAI in hip and knee arthroplasties and the costs of some treatments and prevention methods for these situations. In agreement with the current state of the art, this review identified LOS as the indicator most commonly used to estimate the direct costs of SSIs, and according to some authors, this happens because, in addition to the direct relationship between the LOS and the risk of HAI, the extension of hospitalization days is an easily understood measure either by physicians or by hospital managers, which translates in the consumption of health resources to treat a complication [21,35,43]. According to Plowman [6], patients who developed HAI remained in hospital 2.5 times longer and incurred hospital costs almost three times higher, when compared with an uninfected patient who underwent the same surgical procedure.…”
Section: Discussionmentioning
confidence: 57%
“…According to Iribarren et al [28], in cases of arthroplasty infection, only the antimicrobial's additional costs was about $2421 per patient treated. According to Dal-Paz et al [35], the additional costs in antibiotic therapy and laboratory tests to treat infections of a knee replacement, were approximately $600 per patient.…”
Section: Kneementioning
confidence: 99%
“…A study conducted in Brazil evaluated the costs associated with SSI after total knee arthroplasty in a tertiary public hospital. The additional direct costs of treating infections after total knee arthroplasty were US$ 91 843.75 in total and US$ 2701.29 per patient (Dal-Paz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies did not break down the extent to which each cost component makes up the costs of SSI and non-SSI patients. Where cost components were reported in studies, it either included both SSI and non-SSI patients [55,59,65] or was limited to only SSI patients [53,54,61].…”
Section: Plos Onementioning
confidence: 99%